Digitalization Strategy of the Tourism and Culture Office for Promoting Local Culture in Pandeglang Regency - Nazmudin Nazmudin; Budi Sihabudin; Ratu Elia Jamil (HK-Publishing, 2025)
The digitalization strategy for promoting local culture represents an effort by the Pandeglang Regency Tourism and Culture Office to introduce and preserve local culture while expanding the reach of information about it to the public. The Office utilizes various digital platforms—such as its official website, Instagram, Facebook, TikTok, and YouTube—as media to promote local culture. This study employs Fred R. David’s strategy theory, encompassing strategy formulation, implementation, and evaluation. A descriptive qualitative research method was used, with data collected through interviews, observation, and documentation. The results indicate that the digitalization strategy for promoting local culture in Pandeglang Regency has been implemented quite effectively. This is evidenced by the use of various digital media, collaborations with cultural communities and art studios, and the presentation of promotional content that successfully enhances information dissemination, public knowledge, and participation in cultural activities. However, implementation faces several challenges, such as budget constraints, a shortage of personnel with digital competencies, limited supporting infrastructure, and low levels of public engagement with promotional content published on social media. Conversely, factors supporting the digitalization strategy include organizational commitment to using digital media, inter-divisional cooperation, collaborations with cultural communities and art studios, and high public enthusiasm for cultural activities. Therefore, the Pandeglang Regency Tourism and Culture Office's digitalization strategy requires strengthening through human resource capacity building, the provision of supporting facilities, optimized digital media management, and budgetary support to ensure that the promotion of local culture becomes more effective, innovative, and sustainable. Keywords: Strategy; Digitalization; Tourism and Culture Office; Cultural Promotion